2015
DOI: 10.1017/s1368980015000294
|View full text |Cite
|
Sign up to set email alerts
|

A treelet transform analysis to relate nutrient patterns to the risk of hormonal receptor-defined breast cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC)

Abstract: Pattern analysis has emerged as a tool to depict the role of multiple nutrients/foods in relation to health outcomes. The present study aimed at extracting nutrient patterns with respect to breast cancer (BC) aetiology. Nutrient patterns were derived with treelet transform (TT) and related to BC risk. TT was applied to twenty-three log-transformed nutrient densities from dietary questionnaires. Hazard ratios (HR) and 95 % confidence intervals computed using Cox proportional hazards models quantified the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 84 publications
(151 reference statements)
0
21
0
1
Order By: Relevance
“…The initial search resulted in 136 articles, of which 102 articles were excluded at the title and abstract level. Thirty-four full-length articles were selected for further evaluation and 18 of these were excluded for the following reasons: examined diet as a predictor of breast density not cancer (n=3) (24)(25)(26), the combined effect of diet and physical activity was studied (n=2) (27,28), statistical methods other than those specified in our inclusion criteria were used (n=2) (29,30), and evaluated various forms of vegetarian diet (derived without using any dietary index or factor analysis) (n=1) (31), hormone levels rather than diet were studied (n=3) (32)(33)(34), the effect of diet on breast cancer markers at the molecular level were studied (n=5) (35)(36)(37)(38)(39), assessed the dietary intake of women during their adolescent years (n=1) (40), used an average/reference dietary pattern to derive the risk estimates (n=1) (41), one paper was identified by hand searching the selected articles (42). This resulted in the selection of 17 original research studies published between January 2013 and May 2017 (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), where 13 of these used the posteriori approach while 2 of the 13 also included an a priori approach to identify dietary patterns.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search resulted in 136 articles, of which 102 articles were excluded at the title and abstract level. Thirty-four full-length articles were selected for further evaluation and 18 of these were excluded for the following reasons: examined diet as a predictor of breast density not cancer (n=3) (24)(25)(26), the combined effect of diet and physical activity was studied (n=2) (27,28), statistical methods other than those specified in our inclusion criteria were used (n=2) (29,30), and evaluated various forms of vegetarian diet (derived without using any dietary index or factor analysis) (n=1) (31), hormone levels rather than diet were studied (n=3) (32)(33)(34), the effect of diet on breast cancer markers at the molecular level were studied (n=5) (35)(36)(37)(38)(39), assessed the dietary intake of women during their adolescent years (n=1) (40), used an average/reference dietary pattern to derive the risk estimates (n=1) (41), one paper was identified by hand searching the selected articles (42). This resulted in the selection of 17 original research studies published between January 2013 and May 2017 (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58), where 13 of these used the posteriori approach while 2 of the 13 also included an a priori approach to identify dietary patterns.…”
Section: Resultsmentioning
confidence: 99%
“…To inform the choice of number of factors to retain and the corresponding cut‐level, we ran treelet transform for different numbers of retained components (1–10), identified the optimal cut‐level for each (ranging from 97 to 104) using cross‐validation, inspected scree plots (Supporting Information Fig. S1) and assessed pattern interpretability . The final treelet transform was then computed specifying the number of components to retain and the lowest optimal cut‐level.…”
Section: Methodsmentioning
confidence: 99%
“…S1) 17 and assessed pattern interpretability. 18 The final treelet transform was then computed specifying the number of components to retain and the lowest optimal cut-level. Finally, component scores were calculated for all participants.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In addition, they compared total retinol intake, considering the highest value approximately 6000 mg/day and the lowest intake around 1000 mg/day. They analyzed 24 studies and found a 6% reduction in the risk of developing breast cancer (HR grouped)= 0.94, 95% CI= 0.89-0.99, p= 0.01) 26 .…”
Section: Discussionmentioning
confidence: 99%